2005
DOI: 10.1021/jf051145y
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR Investigation of Cell Wall Polysaccharides from Cereal Grains. Arabinoxylan Infrared Assignment

Abstract: The FT-IR fingerprint of wheat endosperm arabinoxylan (AX) was investigated using a set of polysaccharides exhibiting variation of their degree of substitution and xylo-oligosaccharides comprising xylose units mono- or disubstituted by arabinose residues. Substitution of the xylose backbone by arabinose side units was more particularly studied in the 1000-800 cm(-1) spectral region, by taking advantage of second-derivative enhancement. The 920-1020 cm(-1) spectral region revealed two absorption bands at 984 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 35 publications
14
92
0
9
Order By: Relevance
“…The spectrum of neat RAX ( Figure 6) shows a strong absorption band at 1042 cm −1 , which is due to C-OH bending. 35,36 A weak absorption band at 900 cm −1 is characteristic of β-(1→4) glycosidic linkages between the xylose units in the RAX structure. A low intensity amide I absorption band appears at approximately 1651 cm −1 , which is consistent with a low level of protein contamination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The spectrum of neat RAX ( Figure 6) shows a strong absorption band at 1042 cm −1 , which is due to C-OH bending. 35,36 A weak absorption band at 900 cm −1 is characteristic of β-(1→4) glycosidic linkages between the xylose units in the RAX structure. A low intensity amide I absorption band appears at approximately 1651 cm −1 , which is consistent with a low level of protein contamination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar to the data analysis in NIR study, Tamaki and Mazza [89] employed FTIR-PLS to investigate carbohydrate content and lignin as well as extractives, and the results showed good or excellent predictive ability [90]. Along with PCA, FTIR was used for investigating the fine structural features of arabinoxylan in wheat, although the removal of starch was necessary because of its overlapped bands with arabinoxylan [91]. Allison et al [92] suggested that nitrogen content and alkali index in energy grass could be predicted accurately with FTIR-PLS.…”
Section: Biomass Analysis Via Fourier Transform Mid-infrared Spectrosmentioning
confidence: 99%
“…A partir desta técnica consegue-se identificar diferentes grupos funcionais presentes nos microrganismos. Vários estudos foram realizados sobre a caracterização da composição de diferentes microrganismos (Robert et al, 2005;Garip et al, 2009;Ammanann e Brandl, 2011;Ramos-Escobedo et al, 2016). Bueno et al (2011) caracterizaram a composição da bactéria R. opacus (Tabela 9).…”
Section: Uso De Microrganismos No Processamento Industrialunclassified
“…(Banyay et al, 2003;Bueno et al, 2008;Garip et al, 2009). Também é possível observar as bandas de menor intensidade de 2924 e 2853 cm -1 pertencentes às vibrações assimétricas e simétricas dos radicais CH 2 que estão presentes nos lipídeos, proteínas, carboidratos e ácidos nucléicos (Melin et al, 2004;Robert et al, 2005;Bueno et al, 2008). Por outro lado, a banda de absorção próxima a 1746 cm -1 corresponde à vibração do estiramento do grupo funcional C=O encontrado em lipídeos e triglicerídeos (Garip et al, 2009).…”
Section: Espectroscopia No Infravermelho -Ftirunclassified
See 1 more Smart Citation